Evaluation of a low-intensity pulsed ultrasound for chronic prostatitis type IIIb/chronic pelvic pain syndrome: a randomized controlled trial - Huang, Jiahao; Liao, Zedong; Zhao, Shankun; Lv, Bodong; Liang, Ke (Frontiers in Reproductive Health, 2025)
BackgroundChronic prostatitis type IIIb/chronic pelvic pain syndrome (CP/CPPS) poses significant therapeutic challenges. This study aimed to investigate and compare the clinical efficacy and safety of low-intensity pulsed ultrasound (LIPUS) versus tamsulosin for treating CP/CPPS.MethodsIn this randomized controlled trial, 65 patients with CP/CPPS were allocated to two groups. Group A (n = 35) received LIPUS treatment twice weekly, while Group B (n = 30) received tamsulosin sustained-release capsules (0.2 mg, once nightly). The treatment duration was four weeks for all patients. Outcomes were assessed using the National Institutes of Health Chronic Prostatitis Symptom Index (NIH-CPSI), Self-Rating Anxiety Scale (SAS), and International Index of Erectile Function-5 (IIEF-5) at baseline and 4 weeks post-intervention.ResultsAfter 4 weeks, both groups showed significant improvements in all NIH-CPSI domains (pain, urinary, quality of life), SAS, and IIEF-5 scores compared to baseline (all P < 0.05). Group A demonstrated significantly greater improvement in pain symptoms than Group B (P < 0.05), whereas Group B showed superior improvement in urinary symptoms compared to Group A (P < 0.05). No statistically significant differences were found between the groups for the remaining symptom domains (P > 0.05).ConclusionBoth LIPUS and tamsulosin significantly alleviated CP/CPPS-related symptoms with a favorable safety profile. LIPUS was more effective for pain relief, while tamsulosin was superior for urinary symptoms. Combination therapy may represent a promising approach for managing CP/CPPS.